(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
There is growing evidence that a lack of mastery of the English language causes negative academic consequences for learners. Poor performance of learners in national examinations in some countries, including Namibia, where English is the medium of instruction, has been attributed to low proficiency in English. Studies have also shown that there is often misalignment between what is intended to be taught in the classroom, and what is actually taught. Therefore, the purpose of this study was to explore whether teachers implemented intended Grade 10 ESL learning objectives, specifically in terms of content coverage in their classrooms. The study used a mixed method sequential explanatory design. Quantitative data was collected by questionnaire from thirty teachers of English as Second Language (ESL) at public schools in Windhoek. For the qualitative phase of the study, four teachers were interviewed. The study revealed that teachers do not implement all the intended Grade 10 ESL learning objectives in their classrooms. This ultimately compromises learners’ opportunity to learn and attain academic success.